1992
DOI: 10.1149/1.2221174
|View full text |Cite
|
Sign up to set email alerts
|

Hall Effect and Resistivity Characterization of Doped, Electrodeposited CdSe

Abstract: Doped CdSe thin films were electrodeposited onto indium-tin oxide (ITO) substrates that were pretreated with a thin layer of Se, Cd, or In. Hall effect and resistivity measurements were performed to determine the effects of doping on the resistivity, carrier concentration and carrier mobility. The data varied in a systematic fashion that correlated with the substrate treatment and doping procedures. Carrier concentrations ranged from 10 j ~to 10 ~ cm ', and the el ectrical resistivities were measured in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…From the measurement of cross-plane resistance of the CdSe film, the conductivity has been found to be 0.02 ohm -~ em -~. Employing the values of N D, the mobility of the electrons is found to be 2.4 em 2 V -m see -m. This value is in agreement within the range of values reported (Wynands and Cocivera 1992) for the electrodeposited CdSe films.…”
Section: 3 Results and Discussionsupporting
confidence: 92%
“…From the measurement of cross-plane resistance of the CdSe film, the conductivity has been found to be 0.02 ohm -~ em -~. Employing the values of N D, the mobility of the electrons is found to be 2.4 em 2 V -m see -m. This value is in agreement within the range of values reported (Wynands and Cocivera 1992) for the electrodeposited CdSe films.…”
Section: 3 Results and Discussionsupporting
confidence: 92%
“…The nanocrystalline films prepared in this work are comparable to polycrystalline thin films of CdSe formed by evaporation and electrodeposition. 44 , 49 52 These films have electron mobilities ranging from 3 to 100 cm 2 /(Vs) and carrier concentrations ranging from 10 11 to 10 18 cm –3 , which are sensitive to the grain size, annealing temperature, and are enhanced by doping with indium. 47 , 53 , 54 In these studies, the grain size in the high-performance materials approaches 100 nm; however, our work clearly demonstrates that strong electronic coupling between nanocrystalline grains (<5 nm) can reliably produce films with comparably high carrier mobilities (10–20 cm 2 /(Vs)) and low carrier concentrations (10 16 cm –3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This defective structure may be caused by the voids that separate nanocrystals from one another and from the substrate or by the high concentration of dopants. For example, previous studies of II–VI semiconductors have shown that selenium vacancies and chloride dopants , give rise to an increased carrier concentration and defect density. In the present study, these structures may form because of the relatively high chloride content (3–8 atom %, Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Wyands and Cocivera [88] electrodeposited doped CdSe films and showed that it could be doped via diffusion of Se, Cd, or In during the postdeposition anneal. The Se, Cd, or In was prepared as a layer on the indium tin oxide substrate prior to deposition.…”
Section: Cadmium Selenide (Cdse)mentioning
confidence: 99%
“…Murali and co-workers [86] and Subramanian and coworkers [87] used a pulsed deposition technique to obtain CdSe at room temperature on SiO 2 and Ti substrates using a bath of 0.5 M CdSO 4 and 0.1 M SeO 2 . Wyands and Cocivera [88] electrodeposited doped CdSe films and showed that it could be doped via diffusion of Se, Cd, or In during the postdeposition anneal. The Se, Cd, or In was prepared as a layer on the indium tin oxide substrate prior to deposition.…”
Section: ð14:9þmentioning
confidence: 99%